Discoursal Function of Phonological Patterns in Poetic Texts: Implications for (UN-) Translatability of Poetry - Lotfipour-Saedi, Kazem (Meta, 2005)
AbstractPoetic text, as a literary genre, is distinct from non-literary text because of the special effect it can have on the reader and this special effect in literature-text, as a whole, has been argued to be a function of the special literary forms imposed upon the ordinary language patterns in the literaturetext. Among these special forms, this paper will focus on phonological patterns in poetic texts.Phonological patterns (rhyming, alliteration, assonance, etc.), as special textual tools, can be argued to achieve various special discoursal effects. This paper will analyze a few pieces of poetic text to demonstrate how the phonological patterns employed in them could enhance the textual theme by introducing “defamiliarized” or “dehabitualized” cohesive networks across the text and by reiterating the concepts introduced by the lexical locality of the phonological patterns. The paper will then discuss the implications for the (un-) translatability of poetic texts. Translating poetry does not merely mean producing a text, in TL, which carries rhyming patterns. The TL text should also be equal to SL in terms of the type and degree of special literary effect. For this purpose, the rhyming patterns, due to the special textual function they assume in poetry, should be placed upon the same lexical locality in both SL and TL, a requirement which can hardly be achieved due to the non-isomorphism of sound-meaning relationship across languages.